Pengembangan Tenaga Kependidikan Di Ma Asih Putera - Badrudin Badrudin; Ari Daryani; Desi Safitri (Departement of Mathematics Education, 2024)
Educational human resources, including educators and education personnel, must continue to keep up with developments in order to be able to provide modern, high-quality education and learning that is not outdated compared to other nations. Quality education will produce quality educational output, which is able to compete with other nations. Educators and teaching staff must develop sustainably. Education and training can be used to develop teaching and educational staff. Through development, the potential resources of teaching and educational staff can be guided, nurtured and developed to improve their knowledge, skills and quality of performance in carrying out learning, so that educational professionalism can be realized.